Strategi Multiplikasi Kepemimpinan Gereja Lokal di Era Digital (Jurnal Pendidikan Agama dan Teologi, 2025)
The digital era presents both challenges and opportunities for local church ministry. Sustainable leadership strategies must be wisely prepared by church leaders—remaining firmly rooted in the Word of God while effectively adapting to technological advancements. This paper aims to outline a process that can be implemented by churches in general, based on the author’s experience in a local church in Jakarta and insights from relevant literature. The five key processes include: (1) Transformation of Leadership Paradigms, (2) Identification and Recruitment of Potential Leaders, (3) Development and Discipleship of Future Leaders, (4) Exemplary Leadership Character, and (5) Implementation of Mentoring and Apprenticeship. Through these processes, it is expected that all church leadership components will be able to participate more effectively in ministry (1 Timothy 1:12), with a leadership model that aligns with the needs of times.